Securing defense critical minerals: challenges and U.S. strategic responses in an evolving geopolitical landscape - Vivoda, Vlado; Matthews, Ron; Andresen, Jensine (Taylor & Francis, 2025)
The growing dependence on critical minerals (CMs) for advanced military technologies presents significant and escalating challenges for the United States (U.S.) and its allies. As global competition intensifies and supply chains remain vulnerable to geopolitical disruptions, securing a stable supply of defense CMs has become a top strategic priority. This article identifies key defense CMs, emphasizing their dual-use nature and the risks posed by reliance on adversarial nations such as China and Russia. It analyzes U.S. strategic responses and offers recommendations for balancing national security, economic feasibility, and sustainability in managing defense CM supply chains using a comprehensive approach.
Keywords: 44 Human Society; 4408 Political science